Engineering an immunomodulatory drug-eluting stent to treat laryngotracheal stenosis. (15th March 2019) - Duvvuri, Madhavi; Motz, Kevin; Murphy, Michael; Feeley, Michael; Ding, Dacheng; Lee, Andrew; Elisseeff, Jennifer H.; Hillel, Alexander T.
Abstract : A rapamycin-eluting PLLA-PCL stent is deployed into a diseased mouse trachea to treat laryngotracheal stenosis. Abstract : Objective : Develop a drug-eluting stent construct with a reliable drug-release profile and adequate mechanically stability for a trial in a small animal model of laryngotracheal stenosis (LTS), a debilitating pathologic narrowing of the airway leading to significant shortness of breath. Methods : Biodegradable, biocompatible stents containing 1.0% rapamycin made of PLLA-PCL (70% Poly-l -Lactide and 30% Polycaprolactone blend) and 50 : 50 PDLGA (Poly(dl -lactide- co -glycolide)) were compared. Mechanical strength testing and drug elution rates using high performance liquid chromatography analysis (HPLC) was assessed. Next, efficacy of stent elution on LTS derived scar fibroblasts. Finally, stents were placed in situ in an LTS mouse model. Results : The PLLA-PCL stent construct exhibited greater mechanical strength compared to the PDLGA stent over a 4-week period (Young's Modulus (PLLA-PCL) = 13.82; Young's Modulus (PDLGA) = 4.015). Moreover, the PLLA-PCL stent showed a reliable rapamycin release profile for 6 weeks (30% elution for PLLA-PCL stents compared to <1% elution for PDLGA). Collagen 1 ( p < 0.05) and fibroblast cell proliferation were decreased in vitro when treated with the rapamycin stent. In vivo, the rapamycin stent reduced lamina propria thickness ( p < 0.05) and collagen 1( p < 0.05), collagen 3, TGF-B ( p < 0.05) and a-SMA ( p < 0.05). Conclusions : The PLLA-PCL construct demonstrated superior mechanical strength and greater drug elution compared to PDLGA stents. We demonstrated the feasibility of testing this drug-eluting stent in vivo, showing that the rapamycin-eluting stent treats fibrosis. To our knowledge this is the first study to deploy a drug-eluting stent to treat tracheal pathology in an animal model. Optimization of a rapamycin-eluting PLLA-PCL stent for translational investigation will lead to improved treatment strategies of LTS.